Effect of Methane on the Synthesis of Precipitated Calcium Carbonate via Carbonation Process - M. Lahuri, H; H. Berahim, N; S. Onn, M; G.M. Noh, M; Othman, R (International Journal of Engineering and Technology, 2019)
Precipitated calcium carbonate (PCC) is synthetic calcium carbonate that has high purity of more than 98 wt% of CaCO3 content.  Owing to its unique characteristic whereby its shape and size can be controlled to tailor to various applications, PCC has seen great demands in many industries such as paper, paint, plastic, food, ceramics, cosmetics, pharmaceutical, and many others.  PCC can be synthesized via various methods and the most often used method in industry is via carbonation process.  This process has caught interest of the oil and gas industry for utilizing existing carbon dioxide waste from plant processes.  Precipitation of PCC is carried out using hydrated lime under various conditions at different gas purity (1 mol% CH4 + 99 mol% CO2 , 40 mol% CH4  + 60 mol% CO2 ), different gas flowrate, and different stirring rate.  All experiments are carried out using 1 litre of ionic solution at ambient conditions.  All samples are characterized using Field Emission Scanning Electron Microscopy (FESEM), Particle Size Distribution, X-Ray Diffraction (XRD), and X-Ray Fluorescence (XRF).  FESEM analysis shows different surface morphology for different methane content with calcite formation.  The particle size for all PCC produced at different parameters are comparable at the range 5-9 microns depending on the mixing rate used whereas XRF results indicate very high purity of CaCO3 of more than 99 wt%.